The Effects of Adverse Childhood Experiences and Gender on Developmental Trajectories of Internalizing and Externalizing Outcomes - Leban, Lindsay (Crime & delinquency, 2021)
Adverse Childhood Experiences (ACEs) are linked to problematic outcomes, but it remains unclear how ACEs affect developmental patterns of harmful behavior, and whether this varies by gender. This study examined these relationships among 868 youth participating in the Longitudinal Studies of Child Abuse and Neglect. Group-based trajectory models identified five trajectories of internalizing and six trajectories of externalizing outcomes. Multinomial logistic regression models examined the relationships between ACEs, gender, and the interaction between the two on trajectory group membership. Higher ACEs were associated with elevated internalizing and externalizing trajectories, and boys who experienced higher ACEs were at a heightened risk of exhibiting elevated externalizing trajectories. Findings shed light on the importance of gender in developmental responses to victimization and adversity.